Adolescent men's attitudes and decision making in relation to pregnancy and pregnancy outcomes: An integrative review of the literature from 2010 to 2017. (April 2019) - Kane, Joleen; Lohan, Maria; Kelly, Carmel
Abstract: Introduction: The review updates a previous review conducted in 2010 (Lohan et al.), summarizing the available literature on young men's attitudes and decision-making in the context of addressing two questions: (1) What are adolescent men's attitudes to adolescent pregnancy? (2) What are adolescent men's attitudes and decision-making in relation to pregnancy outcomes? Methods: Using Whittemore and Knafl's process for conducting an integrative review, 38 studies published between 2010 and 2017 reporting on young men's attitudes and decision-making in relation to pregnancy and pregnancy outcomes were analysed. Results: One of the most important conclusions of this review is that the findings of studies can often be contradictory. This is because attitudes to unintended pregnancy, contraception and abortion can be contextual and contingent on the dominant or prevailing social norms and roles within a given time, space or social group. In general, we can conclude that in the vast majority of studies young men perceive actual or potential unintended pregnancies as a life event that will present them with moral and material dilemmas. Conclusions: This review exposes gaps in the academic literature, concerning young men's experiences of unintended pregnancy and pregnancy decision making. This review argues that a greater understanding of young men's experiences when they experience an unintended pregnancy with a partner within a relationship or beyond it is a fundamental first step in offering reproduction and sexual health counselling and services to men. As it stands, we do not yet have a significant body of literature to inform practice development.